Civil war & genocide - Howell, Izzi (Our world in crisis, 2018)
Since the end of the Second World War in 1945, most wars have been civil wars. This book considers how civil wars start, how they are funded and fought and the catastrophic effects they have on the civilians living in the countries involved. It also looks at the atrocities described as genocides, the attempts to destroy an ethnic, religious, national or racial group. It asks readers to think about what they can do to help victims and their families, such as supporting charities who help people to find sustainable ways of living in the aftermath of a civil war.